ANALISA SISTEM PNEUMATIK UNTUK PENGGERAK ALAT PANEN KELAPA SAWIT ( TEMBILANG DAN SABIT ) - Legisnal Hakim (Jurnal APTEK, 2009)
Pneumatic is a fluid power system, that the energy source from the air pressure in compressor machine, where the air store in the tank.The air pressure to activate the pneumatic system is about 1 – 10 bar. Generally the pressure to made power is about 6 – 8 bar, and to make bigger power about 8 – 10 bar. The force in pneumatic system is determine in this machin. It is depent on wide of actuator linear. Wider the actuator it is bigger energy produced and have a better work will bw done. Force that produced by actuator fold with the piston step and devide by the time it is the power that need to harvest the palm. To make this machine work it is need control valve, it valve to control direction, the flow control valve and pressure control valve